Isolation Protocols for Mitigate Influenza in Children - Berker Okay; Cansu Tatar Atamanalp; Fahrettin Aydın; Ozan Hayzaran; Elif Özcan; Nahid Ahmadian; Ardıl Akıntürk; Zeynep Üze Okay; Kamil Şahin; Mahmut Caner Us; Gülşen Akkoç (Çocuk Dergisi)
Objective: Influenza, which is characterized by febrile nature and acute respiratory manifestations, poses a significant threat to children with respect to morbidity and mortality. This study aimed to assess influenza infection data among children during periods of enforced isolation and subsequently when these measures were lifted. Methods: This retrospective cross-sectional study categorized patients into two groups: i) influenza direct fluorescent antibody test (DFT) positive patients admitted between June 16, 2021 and June 15, 2022, when isolation measures were in effect (Group 1) and ii) influenza DFT-positive patients admitted between June 16, 2022 and June 15, 2023, when isolation measures were lifted (Group 2). Results: Influenza A was predominant in Group 1, whereas influenza A and B were more evenly distributed in Group 2, demonstrating a statistically significant difference (p<0.001). The incidence of moderate-to-severe disease was significantly higher in Group 2 than in Group 1 (p<0.001). Groups 1 and 2 differed significantly in terms of hospitalization duration and clinical recovery time (5 [1–7] days vs. 7 [3–9] days, **P<0.001 and 3 [1–4] days vs. 5 [4–7] days, p<0.001, respectively). The analysis of monthly infection distribution revealed a peak occurring 3 months earlier in Group 2 than in Group 1. In Group 1, compliance rates to vaccination recommendations by physicians and pediatricians were 33% and 58%, respectively, whereas compliance rates in Group 2 were 31.5% and 43.7%, respectively. Conclusions: Implementing basic measures such as hand hygiene and mask-wearing can mitigate viral outbreaks. Elevating the rate of physician recommended vaccinations can potentially alleviate disease burden and mitigate disease severity.